2021
DOI: 10.1002/jia2.25739
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the epidemic consequences of HIV prevention gaps among key populations

Abstract: Introduction HIV epidemic appraisals are used to characterize heterogeneity and inequities in the context of the HIV pandemic and the response. However, classic measures used in appraisals have been shown to underestimate disproportionate risks of onward transmission, particularly among key populations. In response, a growing number of modelling studies have quantified the consequences of unmet prevention and treatment needs (prevention gaps) among key populations as a transmission population attributable frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The SANAC commissions external evaluators to conduct the NSP Mid-Term Review and End-Term Review. 15 , 31 The reviews take a highly consultative and participatory approach in which several stakeholders contribute, with a central multisectoral steering committee providing oversight and guidance. Before finalisation and publishing of reports, validation meetings/workshops are held where stakeholders give direct feedback on the findings of the report as well as provide information that might be lacking to be included in the reviews.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SANAC commissions external evaluators to conduct the NSP Mid-Term Review and End-Term Review. 15 , 31 The reviews take a highly consultative and participatory approach in which several stakeholders contribute, with a central multisectoral steering committee providing oversight and guidance. Before finalisation and publishing of reports, validation meetings/workshops are held where stakeholders give direct feedback on the findings of the report as well as provide information that might be lacking to be included in the reviews.…”
Section: Resultsmentioning
confidence: 99%
“…Not addressing the unmet HIV prevention and treatments needs of KPs has negative epidemic consequences. 10 , 31 For example, it is estimated that nearly 50% of HIV infections between 2020 and 2029 would stem from the unmet HIV prevention and treatment needs of FSWs and their clients. 31 …”
Section: Discussionmentioning
confidence: 99%
“…Substantial research has demonstrated that this cross-sectional representation of HIV acquisition poorly quantifies the epidemiological impacts of effective prevention among key populations by not reflecting network effects and the potential to avoid onward transmission. 15,19,47,48 Counterfactual-based metrics such as the transmission preventable attributable fraction or intervention scenario analysis, whose counterfactual scenario accounts for projected cumulative incidence in all population groups over a longer time horizon, better reflect the benefits of HIV prevention efforts among key populations. 17,[39][40][41] Our finding that mathematical models indicated a lower proportion of infections among key populations than assumed by UNAIDS does not undermine modeling evidence for prioritized interventions among these populations; the same models reporting results in this analysis have consistently found large epidemiologic impact and cost-effectiveness for interventions averting transmission among key populations.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of key populations in generalized HIV epidemics has historically been underestimated, largely due to failing to consider differing transmission dynamics [ 8 ]. Evidence suggests that unmet prevention and treatment needs among key populations contribute the highest population‐level long‐term risk of onward transmission [ 9 , 10 ]. Thus, allocating more resources towards filling the “prevention gaps” among key populations could produce the most cost‐effective programming [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%